AB1361 Diagnostic and therapeutic delay of rheumathoid artritis patients in catalonia (spain) and their relationship with specialized healthcare units. The audit study. (23rd January 2014) - Gόmez Caballero, M.E.; Corominas, H.; Narváez, J.; Torrente, V.; de la Fuente de Dios, D.; Campoy, E.; Clavaguera, T.; Morlà, R.; Roig-Vilaseca, D.; Arasa, X.; Díaz-Torné, C.; Salvador, G.; et al.
Abstract : Background: The diagnosis and therapeutic approach to early onset rheumatoid arthritis (RA) patients may be influenced by their access to specialized healthcare units. Objectives: To assess diagnostic and therapeutic delays in RA in Catalonia (Spain) and their relationship with patient's access to specialized healthcare units. Methods: We carried out a cross-sectional epidemiological survey in 19 Catalonian Rheumatology Centres. Ten consecutive patients newly diagnosed with RA (according to physician criteria) during 2009 and 2010 were recruited from each centre. Together with demographic and clinical variables, several parameters related to diagnostic delay were recorded: 1) Time from first symptom to first rheumatologist appointment, 2) Referral time from General Practitioner (GP) evaluation to first rheumatologist appointment, 3) Time from first symptom onset to final RA diagnosis, 4) Time from first symptom to first DMARD started. The presence/absence of specialized healthcare units was evaluated in all centres: 1) Early arthritis units (EAU), 2) RA Units (RAU), 3) Rapid/preferential programming for RA, 4) Referral algorithms from GPs 5) Primary care (PC) rheumatology units (RUPC) and 6) Primary care rheumatology advisory programme (RAPPC). Results: 183 patients (51M/132F) were included. Mean age 52.7±14 years, mean disease duration 27.3±20 months. Mean delays from the first symptom were; to first rheumatology appointment 10.2±12.7 months, to final RA diagnosis 11.3±13.2 months, and first DMARD 11.1±12.8 months. 34.4% of patients had access to an EAU, 37.2% to an RA unit, 66.1% were evaluated through rapid appointment programming and 31.1% through GP referral algorithms. RUPC and RAPPC were available for 61.7% and 31.7% of patients, respectively. Time from first symptom to first DMARD was associated with EAU (8.4±10.5 vs 12.6±13.7 without EAU, p=0.015) and there was a trend to significance for PC rheumatology units (9.1±10.3 vs. 12.1±13.7, p=0.056), but there was no association with RA units, rapid appointment programming, PC rheumatology advisory or referral algorithms from GP. EAU were associated with a shorter delay from first symptom to first rheumatology appointment (7.5±10 vs. 11.6±13.7; p=0.016) and to the final RA diagnosis (8.8±11.4 vs 12.6±13.7; p=0.046). RUPC and RAPPC were associated with a shorter time between both first symptom and first GP evaluation and time to final RA diagnosis. Preferential appointment programming and referral algorithms from GP were not associated with significant differences in delays. Conclusions: The mean delay from symptom onset to RA diagnosis or initiation of the first DMARD in Catalonia was 11 months. Patient's access to specialized units, especially early arthritis units, can improve early diagnosis and treatment of RA. Disclosure of Interest: None Declared